Control of Hopf Bifurcation in Autonomous System Based on Washout Filter - Wenju Du; Yandong Chu; Jiangang Zhang; Yingxiang Chang; Jianning Yu; Xinlei An (Journal of Applied Mathematics)
In order to further understand a Lorenz-like system, we study the stability of the equilibrium points and the existence of Hopf bifurcation by center manifold theorem and normal form theory. More precisely, we designed a washout controller such that the equilibrium E0 undergoes a controllable Hopf bifurcation, and by adjusting the controller parameters, we delayed Hopf bifurcation phenomenon of the equilibrium E+. Besides, numerical simulation is given to illustrate the theoretical analysis. Finally, two possible electronic circuits are given to realize the uncontrolled and the controlled systems.